A review of ovarian teratoma in Hospital Universiti Sains Malaysia ten years experience : 2003 to 2012 - Gada, Abdullah Nasiru (2015)
Introduction Ovarian cancer is the fourth most common cancer among women in United Kingdom (UK) and in Malaysia. It constituted 6.5% of total female cancer with age standardized incidence rate (ASR) of 8.6 per 100,000, and is a major source of morbidity and mortality among women coming only after cancers of lungs, breast and colon in Malaysia. Mature ovarian teratoma is commonly benign; however it is associated with malignant transformation in up to 15% and no reliable preoperative diagnostic procedures to detect this transformation. Immature teratoma represents 3% of total ovarian teratoma but constitutes 20% of germ cell malignancies, it occurs commonly among women below 20 years old and has tendency of recurrence. Fertility preservation approach of management is highly crucial but in advance stage may be difficult and occasionally the fatal complication associated with chemotherapy is a concern. Objective We aim to review the clinico-pathological pattern and outcome of management of ovarian teratoma patients in Hospital Universiti Malaysia (HUSM). Methodology A total of 160 women diagnosed with ovarian teratoma and managed in HUSM from 2003 to 2012 were reviewed retrospectively. List of patients with confirmed histological diagnosis was obtained from pathology department record and their folders were traced, data collected and analyzed using SPSS 21 software (Inc., Chicago, USA). Results Ovarian teratoma is seen from 4 years to 75 years old women and commonest among 21-40 years age group (59.4%). Majority were married (74.4%) and most of them never use oral contraceptive pills (OCP), 64% have 1- 4 children and breast fed for at least one year and 53(33.1%) were pregnant during diagnosis. Abdominal mass or distension and abdominal pain were the commonest presenting symptoms in 32 in cases, 45 cases were incidental diagnosis while 18 presented with acute abdomen. 43.1% of the cases were obese. Mature cystic teratoma is the commonest histological type (91.9%), monodermal 3.1%, immature 2.5% while, malignant transformation and mixed germ teratoma have 1.25% each. Ultrasound features were unilateral 108 (67.5%), bilateral 14 (8.8%). There were mixed solid cystic tumors in majority of cases 89(55.6%), 29(18.1%) were pure cystic while 4(2.5%) were pure solid tumors. Only in 38(31.1%) cases had discrete echogenic mass reported. Laparotomy was the commonest surgical approach 114 cases (71.3%), removal of tumor in the same setting during lower segment Caesarean section (LSCS) were 34 cases (21.3%) and laparoscopic approach was 12 cases (7.5%). The rate of spillage was found to be 21.1%, 20.6% and 58.3% for laparotomy, LSCS and laparoscopic approach respectively. Two cases had adjuvant chemotherapy with Bleomycine, Etoposide and Platinum regimen (BEP) involving one case of immature teratoma and the other of mature teratoma with malignant transformation. Follow up period was 3 -60 months and two cases of recurrent mature ovarian teratoma occurred but no chemical peritonitis reported. Conclusion Teratoma is the commonest ovarian tumor in the reproductive age women, however, we found no significant association with factors such as marital status, parity, breast feeding, use of combine oral contraceptive and body mass index despite the presence ofthese factors in majority of our cases, this might be as a result of low power of the study to detect such an association. Fertility conservation is a great concern; ultrasonography is a reliable means for diagnosing and careful selection of patients for expectant management or surgical intervention. This study reveals that majority (122/160) of ovarian teratoma cases had ultrasound done pre operatively and diagnosis of teratoma was suspected or made but only one out of many presumed pathognomic features of teratoma was reported in 38/112 cases. As such there is need to improve in sonographic reporting of suspected cases of ovarian teratoma. Twelve cases of ovarian teratoma had laparoscopic removal of the tumor with 58.3% spillage rate, however none of the cases had a recurrence or chemical peritonitis therefore laparoscopic approach can be consider as an alternative to traditional laparotomy approach.